Irritable bowel syndrome, mental health, and quality of life: Data from a population‐based survey in Germany (SHIP‐Trend‐0). Issue 3 (15th November 2018) - Schauer, Birgit; Grabe, Hans J.; Ittermann, Till; Lerch, Markus M.; Weiss, Frank U.; Mönnikes, Hubert; Völzke, Henry; Enck, Paul; Schwille‐Kiuntke, Juliane
Abstract: Background: Irritable bowel syndrome (IBS) is associated with reduced quality of life and high healthcare costs. This study aimed to assess the prevalence and risk factors for IBS in a general adult population. Methods: The Study of Health in Pomerania (SHIP) is a population‐based cohort study in northeastern Germany. SHIP‐Trend‐0 participants enrolled from 2008 to 2012 were grouped according to Rome III criteria (main criteria: abdominal discomfort or crampy or bloating pain for at least six months plus 2/3 additional criteria). Factors associated with IBS were assessed using survey‐weighted backward stepwise logistic regression. Key Results: The final data set included 4194 records. IBS prevalence was 3.5% (3.0%‐4.2%). Unemployment (OR: 2.02, 1.26‐3.21), headaches (OR: 2.37, 1.59‐3.52), mental quality of life (OR: 0.95 per unit increase, 0.93‐0.97), and interactions between gender and physical quality of life ( P  = 0.004) and gender and alexithymia ( P  = 0.002) predicted IBS probability. The model resulted in a good discrimination (area under the curve = 75.4%) and model fit ( F  = 0.72, P  = 0.69). History of depression (OR: 2.77, 1.94‐3.95), back pain (OR: 2.38, 1.69‐3.35), early trauma (OR: 1.03, 1.02‐1.04), and duration of inpatient treatment within the last twelve months (OR: 1.02, 1.01‐1.04) lost their significance in multivariable analysis. Conclusions & Inferences: IBS prevalence was relatively low compared to other studies. Factors predicting IBS were of biological, psychological, and social nature. The association between IBS and pain in different areas of the body indicates a potential underlying complex somatic symptom disorder. Abstract : Prevalence of irritable bowel syndrome (IBS) is reported to be heterogeneous and depends on the investigated population and the applied diagnostic criteria. This study aimed to assess prevalence and risk factors for IBS in one of the largest representative population‐based studies assessing IBS in Germany. IBS prevalence was comparatively low; predicting IBS, key factors were unemployment, gender, headaches, physical and mental quality of life.